Factors Affecting Intention to Adopt Electric Vehicles in China - Jing , Jin; Yew, Lim Kim; Kowang , Tan Owee; Kiong , Tee Poh; Chen, Yang (International Journal of Accounting and Economics Studies, 2025)
This study utilizes the Extended Theory of Planned Behavior (ETPB) and Perceived Risk Theory frameworks to investigate the factors ‎affecting intention to adopt electric vehicles (EVs) of Chinese consumers. By incorporating environmental concern and financial incentive ‎policy as cognitive and policy predictors beyond traditional TPB variables, this research provides a comprehensive examination of EV (electric cars) adoption behavior while exploring the moderating function of perceived risk. This study seeks to examine the relationships be‎tween environmental concern, financial incentive policy, and intention to adopt EVs, as well as how perceived risk moderates these relationships. It makes a theoretical contribution by extending TPB with cognitive-environmental and external-policy dimensions and exploring complex interaction mechanisms in China’s policy-oriented market. From the practical perspective, the study offers guidance for government ‎policy design and corporate marketing strategies in promoting sustainable transportation and renewable energy adoption. Many studies on ‎EV adoption rely on purely psychological models, while those incorporating cognitive environmental awareness and external-policy factors ‎in the Chinese context remain limited. The goal of this study is to address this knowledge void by providing a thorough understanding of ‎the multi-dimensional factors driving EV adoption decisions in China‎.